2022
DOI: 10.1002/alz.12836
|View full text |Cite
|
Sign up to set email alerts
|

Brain vitamin D forms, cognitive decline, and neuropathology in community‐dwelling older adults

Abstract: Introduction Vitamin D purportedly protects against cognitive decline and dementia based on observational data using circulating 25‐hydroxyvitamin D (25(OH)D). Little is known about vitamin D in the human brain and the association with dementia or neuropathology. Methods Decedents of the Rush Memory and Aging Project (n = 290) had vitamin D concentrations measured in four brain regions. Associations with cognitive and neuropathological outcomes were estimated using linear and logistic regression. Results The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It plays an important role in the developmental upregulation of KCC2 gene expression that is essential for fast synaptic inhibition in adult neurons 40 . Vitamin D can upregulate VDR 41 and purportedly protect against cognitive decline and dementia 42 . However, the binding of one TF alone is rarely enough to directly infer functional effects on the gene expression levels, typically under the combinatorial and dynamic control of multiple TFs.…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role in the developmental upregulation of KCC2 gene expression that is essential for fast synaptic inhibition in adult neurons 40 . Vitamin D can upregulate VDR 41 and purportedly protect against cognitive decline and dementia 42 . However, the binding of one TF alone is rarely enough to directly infer functional effects on the gene expression levels, typically under the combinatorial and dynamic control of multiple TFs.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence supports the role of vitamin D supplementation in preserving cognitive function, especially in older adults [165][166][167]. Research has shown that adequate levels of vitamin D are associated with improved cognitive performance, and supplementation has been found to benefit those with deficiencies [165][166][167].…”
Section: Vitamin Dmentioning
confidence: 94%
“…Clinical evidence supports the role of vitamin D supplementation in preserving cognitive function, especially in older adults [165][166][167]. Research has shown that adequate levels of vitamin D are associated with improved cognitive performance, and supplementation has been found to benefit those with deficiencies [165][166][167]. This is particularly crucial for cerebrovascular health, as vitamin D supports blood flow to the brain and reduces the risk of cerebrovascular diseases, which can impact cognitive abilities [162,163].…”
Section: Vitamin Dmentioning
confidence: 97%
“…A recent article reported measurements of 25(OH)D in the serum and in the brain with respect to mild cognitive impairment or dementia [ 123 ]. This study was conducted among 290 participants in the Descendants of the Rush Memory and Aging Project with a mean age at death of 92 ± 6 years and a mean plasma 25(OH)D concentration of 35 ± 17 ng/mL.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%